A composite solid electrolyte membrane efficient continuous production system, production process and application
Patent Information
- Application Number
- CN202511981059.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-25
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-12-25
AI Technical Summary
[0003]现有紫外固化连续产线面临三大挑战:一是固化环境控制不足,空气中氧分子引发自由基淬灭,导致固化不完全(表面发粘);二是多温区热干扰严重,红外干燥与UV固化温度差异超30℃,传统隔离方式难以维持稳定梯度;三是高填料浆料流变特性复杂,涂布过程粘度波动大,影响膜厚一致性(±5μm以上)
1. 生产效率与产品精度实现突破:上述系统的协同作用,使得生产线速度最高可达10 m/min(传统热固化工艺的5倍以上),并保障膜厚精度在±1.5μm以内(CV值≤2%)。
Smart Images

Figure CN121748497B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state lithium battery materials technology, and more specifically, to a high-efficiency continuous production system, production process and application of composite solid electrolyte membranes. Background Technology
[0002] Solid-state lithium batteries have become a research hotspot in the energy storage field due to their high safety and energy density. Their core component, the composite solid electrolyte membrane, needs to also achieve high ionic conductivity (>10). -4 The film thickness (S / cm) and mechanical strength (>5MPa) are important parameters. Traditional thermosetting processes involve high-temperature (>120℃) and long-term treatment, resulting in slow production speed (<2m / min), high energy consumption, and poor film thickness uniformity (CV value >5%). They are particularly unsuitable for UV-curing systems containing a high proportion of inorganic fillers (>40wt%). Filler sedimentation leads to uneven film structure, and high temperatures can easily trigger organic phase decomposition, reducing ion transport efficiency. There is an urgent need to develop continuous production technologies to overcome efficiency and performance bottlenecks.
[0003] Existing UV curing continuous production lines face three major challenges: First, insufficient control of the curing environment, with oxygen molecules in the air triggering free radical quenching, leading to incomplete curing (sticky surface); second, severe thermal interference across multiple temperature zones, with the temperature difference between infrared drying and UV curing exceeding 30°C, making it difficult to maintain a stable gradient using traditional isolation methods; and third, the complex rheological properties of high-filler slurries, resulting in large viscosity fluctuations during coating and affecting film thickness consistency (above ±5μm). Furthermore, peeling of the cured film from the substrate easily produces microcracks, resulting in a winding yield often below 90%, and mechanical peeling damages the electrolyte structure, reducing dendrite tolerance (<100h).
[0004] In recent years, the industry has attempted to improve reaction efficiency through nitrogen-protected UV curing, but conventional unidirectional airflow makes it difficult to achieve stable control of oxygen content <100ppm. Although the concept of layered curing has been proposed, the lack of precise temperature zone isolation solutions has led to reverse thermal contamination of the UV curing section by the hot air curing zone. At the same time, electrostatic assisted peeling technology is prone to film wrinkling at high speeds (>5m / min) due to uneven electric field distribution. Therefore, there is an urgent need for a continuous production system that integrates gradient temperature control, ultra-low oxygen environment maintenance, intelligent viscosity control, and non-destructive peeling to simultaneously meet the industrialization requirements of high speed (>10m / min), high precision (film thickness CV≤2%), and high performance (dendritic tolerance>500h). Summary of the Invention
[0005] The purpose of this invention is to overcome the aforementioned deficiencies in existing technologies and provide a highly efficient continuous production system, process, and application for composite solid electrolyte membranes. This invention integrates multi-stage curing (infrared drying - ultra-low oxygen UV curing - layered curing) with precise temperature zone isolation (negative pressure air curtain + liftable baffle), combined with a Z-shaped nitrogen flow field and online closed-loop control, along with online viscosity feedback and a laser / UV dual-detection closed-loop system, to achieve spiral microgroove electrostatic stripping and dual-station winding. The production process using this system enables high-filler (>40%) slurry to be produced continuously at a high speed of 10m / min, with a film thickness consistency of ±1.5μm (CV value ≤2%), a 40% reduction in curing energy consumption, ensuring film integrity and a yield of >98%, ultimately obtaining high conductivity (≥1.2×10⁻⁶). -4 Solid electrolyte membranes with high strength (≥8MPa) and long lifespan (dendritic tolerance >500h) and high strength (S / cm).
[0006] To achieve the above objectives, the technical solution of the present invention is as follows: A high-efficiency continuous production system for composite solid electrolyte membranes includes a slurry supply unit, an unwinding unit, a coating unit, a gradient curing unit, and a peeling and rewinding unit. The slurry supply unit includes a slurry processing device, an intermediate buffer tank 3A, and a finished slurry tank 3B connected together; the slurry processing device includes a sand mill 1 and an ultrasonic dispersion tank 2, and the sand mill 1 and the ultrasonic dispersion tank 2 can be selectively connected to the intermediate buffer tank 3A in series or in parallel; the intermediate buffer tank 3A is equipped with an online viscosity feedback system 4 and an additive feeding port, and the online viscosity feedback system 4 is connected to the central controller signal. The unwinding unit includes an unwinding roller, which is used for unwinding the substrate; The coating unit includes a preheating roller 6 and a slot coating die 5 arranged sequentially along the substrate travel direction; the preheating roller 6 is located downstream of the unwinding roller 21 and is used to transport and preheat the substrate; the slot coating die 5 is connected to the outlet of the finished slurry tank 3B and is located on one side of the preheating roller 6, and is used to coat the finished slurry onto the preheated substrate surface on the preheating roller 6 to form a wet film; The gradient curing unit includes a gradient curing chamber, which is provided with an infrared drying zone 7, a UV curing zone 8 and a low-temperature curing zone 9 in sequence along the direction of travel of the coated substrate, for gradient curing of the coated substrate. The infrared drying zone 7 is equipped with a plate-shaped infrared radiator 10; the UV curing zone 8 is equipped with a dual-wavelength LED array 13; and the low-temperature curing zone 9 is equipped with a layered hot air circulation system. The peeling and winding unit includes an electrostatic adsorption roller 19 with spiral microgrooves on its surface and a dual-station winding machine 20, which are used for electrostatic peeling and winding.
[0007] Optionally, the discharge port of the sand mill 1 is connected to the inlet of the intermediate buffer tank 3A via a first feed pipe L1, and to the inlet of the ultrasonic dispersion tank 2 via a first series pipe L3; the discharge port of the ultrasonic dispersion tank 2 is connected to the inlet of the intermediate buffer tank 3A via a second feed pipe L2; the discharge port of the intermediate buffer tank 3A is connected to the inlet of the finished slurry tank 3B via a conveying pipe L4; the intermediate buffer tank 3A is also provided with a first reflux pipe L5 and a second reflux pipe L6, the first reflux pipe L5 being connected to the inlet of the sand mill 1, and the second reflux pipe L6 being connected to the inlet of the ultrasonic dispersion tank 2.
[0008] Optionally, controllable valves are provided on the first feeding pipeline L1, the second feeding pipeline L2, the first series pipeline L3, the conveying pipeline L4, the first return pipeline L5, and the second return pipeline L6.
[0009] Optionally, the controllable valve is operated by a central controller, and by switching its opening and closing states, three slurry pretreatment process paths can be formed: Path 1: Open the controllable valve on the first feed line L1, and close the controllable valves on the first series line L3 and the second feed line L2. The slurry raw material is directly fed into the intermediate buffer tank 3A after being processed by the sand mill 1. This is suitable for slurry systems with high filler hardness, severe initial agglomeration, and requiring strong mechanical crushing, or for scenarios with strict requirements on the final slurry particle size distribution.
[0010] Path 2: Open the controllable valve on the second feed line L2, and close the controllable valves on the first feed line L1 and the first series line L3. The slurry raw material is directly fed into the intermediate buffer tank 3A after being processed by the ultrasonic dispersion tank 2. This is suitable for slurry systems where the filler has been initially dispersed, or which are heat-sensitive and need to avoid excessive mechanical shearing that could cause the system to heat up or structurally damage.
[0011] Path 3: Open the controllable valves on the first series pipeline L3 and the second feed pipeline L2, and close the controllable valve on the first feed pipeline L1. The slurry raw material is sequentially processed through the sand mill 1 and the ultrasonic dispersion tank 2 in series before entering the intermediate buffer tank 3A. This method is suitable for complex systems with high solids content, high viscosity, or containing easily agglomerated nanofillers. Macroscopic crushing is achieved through sand milling, followed by microscopic uniform dispersion through ultrasonication, achieving optimal dispersion results.
[0012] Optionally, the central controller can automatically select and execute the corresponding path based on a preset formula process parameter library or operator input.
[0013] Optionally, the central controller is used to perform graded control on the slurry in the intermediate buffer tank 3A based on the real-time monitoring data of the online viscosity feedback system 4. (a) Precision adjustment mode: If the viscosity value of the slurry is within the preset coating target viscosity range, add the additive into the intermediate buffer tank 3A through the additive feeding port for online precision adjustment until the viscosity stabilizes at the target value. Then, open the controllable valve on the delivery pipeline L4 and pump the adjusted slurry to the finished slurry tank 3B. (b) Reflow and reprocessing mode: If the viscosity value of the slurry is not within the preset coating target viscosity range, control the opening of the controllable valve on the first reflow pipeline L5 or the second reflow pipeline L6 to pump the slurry in the intermediate buffer tank 3A back to the sand mill 1 or the ultrasonic dispersion tank 2 for redispersion treatment.
[0014] Optionally, the preset target viscosity range for coating is 500-2000 cP.
[0015] Optionally, the gradient curing chamber is equipped with a temperature zone isolation component: A negative pressure air curtain 12 is installed between the infrared drying zone 7 and the UV curing zone 8, with a pressure difference of -10 to -50 Pa, to prevent hot air crosstalk. Specifically, a slit-type air-blowing knife is installed along the width of the membrane material on the crossbeam separating the two zones, with its outlet vertically downwards facing the substrate in operation. At the bottom of the corresponding zone, a negative pressure suction groove with the same width as the air-blowing knife is provided. During system operation, the air-blowing knife continuously delivers low-speed, uniform cooling gas downwards, forming an air curtain; simultaneously, the negative pressure suction groove at the bottom uses stronger suction to maintain a stable pressure difference of -10 to -50 Pa in the air curtain area. This design effectively blocks hot air and volatiles in the infrared zone, ensuring clean and stable gas at the inlet of the UV curing zone.
[0016] A liftable ceramic fiber baffle 14 with a thermal conductivity ≤0.05W / m·K is installed between the UV curing zone 8 and the low-temperature curing zone 9 to achieve physical insulation and avoid back-heat contamination. Each temperature zone is independently temperature controlled with a temperature difference ≤±1℃. Specifically, the ceramic fiber baffle 14 is installed on the lifting mechanism (such as an electric push rod or a cylinder-driven guide rail) on the top crossbeam and bottom of the chamber separating the two temperature zones. The baffle is made of ceramic fiber material with a thermal conductivity ≤0.05W / m·K and is designed to completely cover the cross-section of the substrate transmission channel. During normal continuous production, the ceramic fiber baffle 14 is lowered, and its bottom edge is tightly fitted to the bottom structure of the chamber through a high-temperature resistant sealing strip, thereby physically blocking the gas flow and heat exchange between the two temperature zones. This effectively prevents the hot air from the low-temperature curing zone 9 from diffusing back to the temperature-sensitive UV curing zone 8, ensuring that the independent temperature control accuracy of each temperature zone reaches a temperature difference ≤±1℃.
[0017] Optionally, the "liftable" function is controlled by a central controller. When the equipment needs to be stopped for maintenance, cleaning, or re-threading of the substrate, the controller instructs the lifting mechanism to fully raise the ceramic fiber baffle 14, providing an unobstructed passage for operation and greatly improving the operability and maintenance convenience of the equipment.
[0018] Optionally, the temperature of the infrared drying zone 7 and the plate-shaped infrared radiator 10 is controlled at 79.5-80.5℃.
[0019] Optionally, the UV curing zone 8 and the dual-wavelength LED array 13 have wavelengths of 365nm and 395nm respectively; along the travel direction of the coated substrate, a high-irradiation section and a low-irradiation section are sequentially provided; the high-irradiation section is 80-100mW / cm²; the low-irradiation section is 20-40mW / cm², and the irradiation intensity is adjustable in real time.
[0020] Optionally, the UV curing zone is also equipped with a Z-type nitrogen flow field system, including a bidirectional tangential air inlet 17 and a central top-suction exhaust port 16. The flow rate of the bidirectional tangential air inlet 17 is 5-20 L / min, and the airflow velocity of the central top-suction exhaust port 16 is 0.5-2 m / s, maintaining an oxygen content of <50 ppm.
[0021] Optionally, the low-temperature curing zone adopts a layered hot air circulation system, with a hot air jet plate 18 at the bottom, a wind speed of 10-20 m / s, and a wind temperature of 49-51℃; and a micro-negative pressure return air channel at the top, with a negative pressure of -5 to -20 Pa.
[0022] Optionally, the system also includes an online quality monitoring module, comprising: a thickness laser micrometer 11, located at the outlet of the infrared drying zone 7, for real-time monitoring of film thickness; and an ultraviolet imager 15, located at the outlet of the UV curing zone 8, for detecting curing uniformity. Both the thickness laser micrometer 11 and the ultraviolet imager 15 are connected to the central controller, and the detection data is used to provide real-time feedback for adjusting the gap of the slit coating die 5 and the process conditions of each curing zone.
[0023] Optionally, the electrostatic adsorption roller 19 is located downstream of the gradient curing chamber outlet, and the dual-station winding machine 20 is located downstream of the electrostatic adsorption roller 19. The depth of the spiral microgrooves on the surface of the electrostatic adsorption roller 19 is 50-200μm, the spiral angle is 15°-30°, and the voltage of the electrostatic adsorption roller 19 is 0.5-5kV.
[0024] This invention also discloses a high-efficiency continuous production process for composite solid electrolyte membranes, employing the aforementioned high-efficiency continuous production system for composite solid electrolyte membranes, comprising the following steps: (1) After the slurry raw material is processed by the sand mill 1 and / or the ultrasonic dispersion tank 2, it is transported to the intermediate buffer tank 3A. After viscosity adjustment by the linear viscosity feedback system 4 controlled by the central controller signal and the additive feeding port, it is transported to the finished slurry tank 3B for use. (2) The substrate is drawn out by the unwinding roller 21 and preheated to the coating temperature by the preheating roller 6; the slurry stored in the finished slurry tank 3B is conveyed to the slot coating die 5 and coated on the surface of the preheated substrate by the slot coating die 5 to form a wet film. (3) The coated substrate enters the gradient curing chamber and undergoes gradient curing in sequence through the infrared drying zone 7, the UV curing zone 8 and the low temperature curing zone 9; wherein, the infrared drying zone 7 uses a plate-shaped infrared radiator 10 for preliminary drying; the UV curing zone 8 uses a dual-wavelength LED array 13 for irradiation treatment; and the low temperature curing zone 9 uses a layered hot air circulation system for curing treatment. (4) The cured substrate is electrostatically peeled off by an electrostatic adsorption roller 19 with spiral microgrooves on its surface. The peeled film is then wound up by a dual-station winding machine 20 to obtain the composite solid electrolyte membrane.
[0025] Optionally, step (3) specifically includes: placing the coated substrate into a gradient curing chamber, sequentially passing through an infrared drying zone 7, a UV curing zone 8, and a low-temperature curing zone 9; wherein, the processing parameters of the infrared drying zone 7 are: preliminary drying at 79.5-80.5℃ for 1-2 minutes; the processing parameters of the UV curing zone 8 are: under a nitrogen protection environment, controlling the oxygen content to <50ppm, irradiating with a dual-wavelength LED array 13, the dual wavelengths of the dual-wavelength LED array 13 being 365nm and 395nm respectively; along the direction of travel of the coated substrate, a high irradiation section and a low irradiation section are sequentially provided; wherein the intensity of the high irradiation section is 80-100mW / cm², the intensity of the low irradiation section is 20-40mW / cm², and the total irradiation time is 10-30s; the processing parameters of the low-temperature curing zone 9 are: using a layered hot air circulation system, curing at 49-51℃ for 5-10 minutes.
[0026] Optionally, in step (2), the coating temperature is 55-65℃; the thickness of the wet film is 50-200μm.
[0027] Optionally, step (4) specifically includes: applying an adjustable voltage of 0.5-5kV to the electrostatic adsorption roller 19 to achieve low-tension, damage-free peeling; the peeled film is wound up by a dual-station winding machine 20 at a production speed of 5-10m / min and a roll-to-roll yield of >98%.
[0028] Optionally, step (1) specifically includes: the central controller selects and controls the controllable valves on the corresponding pipelines according to the formula characteristics, so that the slurry is processed in one of the following three paths: Path 1: After being processed by the sand mill 1, the slurry enters the intermediate buffer tank 3A through the first feed pipeline L1; Path 2: After being processed by the ultrasonic dispersion tank 2, the slurry enters the intermediate buffer tank 3A through the second feeding pipeline L2; Path 3: The slurry is processed in series by the sand mill 1 and the ultrasonic dispersion tank 2, and then enters the intermediate buffer tank 3A through the second feed pipeline L2.
[0029] Optionally, the viscosity of the slurry entering the intermediate buffer tank 3A is monitored in real time by the online viscosity feedback system 4, and graded control is performed by the central controller. A. If the viscosity is within the preset coating target viscosity range, add the additive into the tank through the additive feeding port until the viscosity stabilizes at the target viscosity value. Then, turn on the delivery pipeline L4 to pump the qualified slurry to the finished slurry tank 3B. B. If the viscosity is not within the preset target viscosity range for coating, control the opening of the controllable valve on the first return pipeline L5 or the second return pipeline L6 to pump the slurry back to the sand mill 1 or the ultrasonic dispersion tank 2 for redispersion treatment. After treatment, return it to the intermediate buffer tank 3A to readjust the viscosity.
[0030] Optionally, the target viscosity value is 500-2000 cP, with an adjustment accuracy of ±5%.
[0031] Optionally, the method further includes temperature control using a temperature zone isolation component: a negative pressure air curtain 12 is provided between the infrared drying zone 7 and the UV curing zone 8, with a pressure difference of -10 to -50 Pa; a liftable ceramic fiber baffle 14 with a thermal conductivity ≤0.05 W / m·K is provided between the UV curing zone 8 and the low-temperature curing zone 9; each temperature zone is independently temperature controlled, with a temperature difference ≤±1℃; Optionally, the method further includes using a Z-type nitrogen flow field system in the UV curing zone to control the curing parameters, with the flow rate of the bidirectional tangential air inlet 17 being 5-20 L / min and the airflow velocity of the central top-suction exhaust port 16 being 0.5-2 m / s, maintaining an oxygen content of <50 ppm. Optionally, the method further includes a hot air jet plate 18 at the lower part of the low-temperature curing zone, with a wind speed of 10-20 m / s and a wind temperature of 49-51℃; and a micro-negative pressure return air channel at the upper part, with a negative pressure of -5 to -20 Pa.
[0032] Optionally, an online quality monitoring module is used for detection during the production process, including: a thickness laser micrometer 11 set at the outlet of the infrared drying zone 7 for real-time monitoring of film thickness; and an ultraviolet imager 15 set at the outlet of the UV curing zone 8 for detecting curing uniformity. Both the thickness laser micrometer 11 and the ultraviolet imager 15 are connected to the central controller signal, and the detection data is used to provide real-time feedback to adjust the gap of the slit coating die 5 and the process conditions of each curing zone.
[0033] The present invention also discloses a high-efficiency continuous production system for composite solid electrolyte membranes as described above, or the application of the high-efficiency continuous production process for composite solid electrolyte membranes as described above in the continuous production of composite solid electrolyte membranes for solid lithium batteries.
[0034] This invention aims to solve industry problems such as low efficiency, poor precision, and unstable performance in the continuous production of high-filler (>40%) UV-curing systems. The core of this invention lies in the innovative integration of an intelligent slurry processing system, a multi-stage precision curing chamber, and a non-destructive peeling and winding system, achieving closed-loop control throughout the entire process through a central controller.
[0035] First, intelligent slurry supply and precise viscosity control. Addressing the complex rheological properties of high-filler slurries, the equipment employs a flexible path design with parallel / series connections between a sand mill and an ultrasonic dispersion tank, and innovatively includes an intermediate buffer tank 3A with dual reflux pipelines (L5, L6). Through real-time monitoring by the online viscosity feedback system 4, the system can intelligently select either a "precision adjustment mode" (adding a trace amount of regulator) or a "reflux reprocessing mode" (returning the slurry to the sand mill or ultrasonic dispersion tank for reprocessing), ensuring that the slurry viscosity input to the coating unit remains stable at 500-2000 cP (±5%), laying the foundation for consistent film thickness from the outset.
[0036] Second, the precise synergy between gradient curing and an ultra-low oxygen environment. The curing chamber is sequentially equipped with three temperature zones: infrared drying (80±0.5℃), UV curing, and low-temperature curing (50±1℃). Key innovations include: 1) Physical isolation using a negative pressure air curtain 12 and a liftable ceramic fiber baffle 14 to ensure temperature fluctuations in each zone are ≤±1℃, eliminating thermal interference; 2) The UV curing zone integrates a dual-wavelength LED array 13 and a unique Z-shaped nitrogen flow field, stably controlling the oxygen content to <50ppm, completely eliminating oxygen inhibition and achieving deep and uniform curing; 3) The curing zone employs layered hot air circulation to improve thermal efficiency. This synergistic design achieves a balance between curing speed and quality.
[0037] Third, high-speed, non-destructive peeling and full-process quality monitoring. Peeling is performed using an electrostatic adsorption roller 19 with spiral microgrooves on its surface. Electrostatic force achieves low-tension, non-mechanically damaged peeling, ensuring film integrity. Combined with a dual-station winding machine 20, continuous production is achieved. Simultaneously, an integrated online quality monitoring module transmits data in real-time to the central controller via a thickness laser micrometer 11 and an ultraviolet imager 15, dynamically adjusting coating and curing parameters to form a closed-loop production system.
[0038] Implementing the embodiments of the present invention will have the following beneficial effects: 1. Breakthrough in production efficiency and product precision: The synergistic effect of the above systems enables the production line speed to reach up to 10 m / min (more than 5 times that of traditional thermosetting processes), while ensuring film thickness accuracy within ±1.5μm (CV value ≤2%).
[0039] 2. Significantly improved overall performance of the electrolyte membrane: The produced composite solid electrolyte membrane possesses both high ionic conductivity (≥1.2×10⁻⁶) and high ionic conductivity (≥1.2×10⁻⁶). -4 It has high tensile strength (≥8MPa) and excellent dendrite resistance (dendrite tolerance time >500h, far exceeding the <100h of traditional processes).
[0040] 3. High production economy and reliability: Closed-loop control and non-destructive peeling increase the roll-to-roll production yield to over 98%, while reducing curing energy consumption by approximately 40%. Intelligent slurry processing and a stable curing environment significantly reduce the scrap rate and equipment maintenance requirements of high-filler systems, providing reliable equipment and process support for the large-scale mass production of solid-state batteries. Attached Figure Description
[0041] Figure 1 This is a schematic diagram of the system of the present invention.
[0042] The components include: 1. Sand mill; 2. Ultrasonic dispersion tank; 3A. Intermediate buffer tank; 3B. Finished slurry tank; 4. Online viscosity feedback system; 5. Slit coating die head; 6. Preheating roller; 7. Infrared drying zone; 8. UV curing zone; 9. Low temperature curing zone; 10. Plate-shaped infrared radiator; 11. Thickness laser micrometer; 12. Negative pressure air curtain; 13. Dual-wavelength LED array; 14. Liftable ceramic fiber baffle; 15. Ultraviolet imager; 16. Central top-suction exhaust port; 17. Bidirectional tangential air inlet; 18. Hot air jet plate; 19. Electrostatic adsorption roller; 20. Dual-station winding machine; 21. Unwinding roller; L1. First feeding pipeline; L2. Second feeding pipeline; L3. First series pipeline; L4. Conveying pipeline; L5. First return pipeline; L6. Second return pipeline. Detailed Implementation
[0043] The present invention will be further described below with reference to specific embodiments, but this does not limit the present invention in any way.
[0044] The slurry formulation (based on the total mass of the slurry, acetonitrile: 90%, solid components: 10%, its internal composition is: LLZO: 20%, PETA: 25%, PEO: 35%, LiTFSI: 16%, borate ester: 2%, initiator: 2%) is used as the uniform raw material in the examples listed in this patent (except for Example 5).
[0045] Example 1 The high-efficiency continuous production system for composite solid electrolyte membranes in this embodiment includes a slurry supply unit, an unwinding unit, a coating unit, a gradient curing unit, and a peeling and rewinding unit.
[0046] The slurry supply unit includes a slurry processing device, an intermediate buffer tank 3A, and a finished slurry tank 3B connected together; the slurry processing device includes a sand mill 1 and an ultrasonic dispersion tank 2, and the sand mill 1 and the ultrasonic dispersion tank 2 can be selectively connected to the intermediate buffer tank 3A in series or in parallel; the intermediate buffer tank 3A is equipped with an online viscosity feedback system 4 and an additive feeding port, and the online viscosity feedback system 4 is connected to the central controller signal. The unwinding unit includes an unwinding roller, which is used to unwind the substrate.
[0047] The coating unit includes a preheating roller 6 and a slot coating die 5 arranged sequentially along the substrate travel direction; the preheating roller 6 is located downstream of the unwinding roller 21 and is used to transport and preheat the substrate; the slot coating die 5 is connected to the outlet of the finished slurry tank 3B and is located on one side of the preheating roller 6, and is used to coat the finished slurry onto the preheated substrate surface on the preheating roller 6 to form a wet film.
[0048] The gradient curing unit includes a gradient curing chamber, which is provided with an infrared drying zone 7, a UV curing zone 8 and a low-temperature curing zone 9 along the direction of travel of the coated substrate, for gradient curing of the coated substrate.
[0049] The infrared drying zone 7 is equipped with a plate-shaped infrared radiator 10; the UV curing zone 8 is equipped with a dual-wavelength LED array 13; and the low-temperature curing zone 9 is equipped with a layered hot air circulation system.
[0050] Peeling and winding unit: includes an electrostatic adsorption roller 19 with spiral microgrooves on its surface and a dual-station winding machine 20, used for electrostatic peeling and winding.
[0051] The discharge port of the sand mill 1 is connected to the inlet of the intermediate buffer tank 3A through the first feed pipe L1, and is connected to the inlet of the ultrasonic dispersion tank 2 through the first series pipe L3; the discharge port of the ultrasonic dispersion tank 2 is connected to the inlet of the intermediate buffer tank 3A through the second feed pipe L2; the discharge port of the intermediate buffer tank 3A is connected to the inlet of the finished slurry tank 3B through the conveying pipe L4; the intermediate buffer tank 3A is also provided with a first reflux pipe L5 and a second reflux pipe L6, the first reflux pipe L5 is connected to the inlet of the sand mill 1, and the second reflux pipe L6 is connected to the inlet of the ultrasonic dispersion tank 2.
[0052] Controllable valves are provided on the first feeding pipeline L1, the first series pipeline L3, the second feeding pipeline L2, the conveying pipeline L4, the first return pipeline L5, and the second return pipeline L6.
[0053] Among them, the controllable valves are operated by a central controller, and by switching their opening and closing states, three slurry pretreatment process paths are formed: Path 1: Open the controllable valve on the first feed line L1, and close the controllable valves on the first series line L3 and the second feed line L2. The slurry raw material is directly fed into the intermediate buffer tank 3A after being processed by the sand mill 1.
[0054] Path 2: Open the controllable valve on the second feed line L2, close the controllable valves on the first feed line L1 and the first series line L3, and the slurry raw material enters the intermediate buffer tank 3A directly after being treated by the ultrasonic dispersion tank 2.
[0055] Path 3: Open the controllable valves on the first series pipeline L3 and the second feed pipeline L2, and close the controllable valve on the first feed pipeline L1. The slurry raw material is processed in series by the sand mill 1 and the ultrasonic dispersion tank 2, and then enters the intermediate buffer tank 3A.
[0056] The central controller is used to perform graded control on the slurry in the intermediate buffer tank 3A based on real-time monitoring data from the online viscosity feedback system 4. (a) Precision adjustment mode: If the viscosity of the slurry is within the preset target viscosity range for coating (500-2000 cP), control the additive feeding port to add additives into the intermediate buffer tank 3A for online precision adjustment until the viscosity stabilizes at the target value. Then open the controllable valve on the delivery pipeline L4 to pump the adjusted slurry to the finished slurry tank 3B. (b) Reflow and reprocessing mode: If the viscosity value of the slurry is not within the preset coating target viscosity range (500-2000cP), control the opening of the controllable valve on the first reflow pipeline L5 or the second reflow pipeline L6 to pump the slurry in the intermediate buffer tank 3A back to the sand mill 1 or the ultrasonic dispersion tank 2 for redispersion treatment.
[0057] The gradient curing chamber is equipped with temperature zone isolation components: a negative pressure air curtain 12 is installed between the infrared drying zone 7 and the UV curing zone 8, with a pressure difference of -10 to -50 Pa. A liftable ceramic fiber baffle 14 with a thermal conductivity ≤0.05 W / m·K is installed between the UV curing zone 8 and the low-temperature curing zone 9 to achieve physical heat insulation and avoid reverse heat contamination; each temperature zone is independently temperature controlled, with a temperature difference ≤±1℃.
[0058] In the infrared drying zone 7, the temperature of the plate-shaped infrared radiator 10 is controlled at 79.5-80.5℃.
[0059] Among them, the UV curing zone 8 and the dual-wavelength LED array 13 have wavelengths of 365nm and 395nm respectively; along the direction of travel of the coated substrate, there are high-irradiation section and low-irradiation section in sequence; the high-irradiation section is 80-100mW / cm²; the low-irradiation section is 20-40mW / cm², and the irradiation intensity can be adjusted in real time.
[0060] The UV curing zone is also equipped with a Z-type nitrogen flow field system, including a bidirectional tangential air inlet 17 and a central top-suction exhaust port 16. The flow rate of the bidirectional tangential air inlet 17 is 5-20 L / min, and the airflow velocity of the central top-suction exhaust port 16 is 0.5-2 m / s, maintaining an oxygen content of <50 ppm.
[0061] The low-temperature curing zone employs a layered hot air circulation system, with a hot air jet plate 18 at the bottom, a wind speed of 10-20 m / s, and a wind temperature of 49-51℃; and a slightly negative pressure return air channel at the top, with a negative pressure of -5 to -20 Pa.
[0062] The system also includes an online quality monitoring module, comprising: a thickness laser micrometer 11, located at the outlet of the infrared drying zone 7, for real-time monitoring of film thickness; and an ultraviolet imager 15, located at the outlet of the UV curing zone 8, for detecting curing uniformity. Both the thickness laser micrometer 11 and the ultraviolet imager 15 are connected to the central controller, and the detection data is used to provide real-time feedback for adjusting the gap of the slit coating die 5 and the process conditions of each curing zone.
[0063] Among them, the electrostatic adsorption roller 19 is located downstream of the gradient curing chamber outlet, and the dual-station winding machine 20 is located downstream of the electrostatic adsorption roller 19. The depth of the spiral microgrooves on the surface of the electrostatic adsorption roller 19 is 50-200μm, the spiral angle is 15°-30°, and the voltage of the electrostatic adsorption roller 19 is 0.5-5kV.
[0064] Example 2 The high-efficiency continuous production process for composite solid electrolyte membranes in this embodiment adopts the high-efficiency continuous production system for composite solid electrolyte membranes as described in Example 1, and includes the following steps: (1) After the slurry raw material is processed by the sand mill 1, it enters the intermediate buffer tank 3A through the first feed pipeline L1. The viscosity is monitored in real time by the online viscosity feedback system 4 and is 1900 cP. Acetonitrile is added into the tank through the additive feed port, and the central controller performs graded control to adjust the target viscosity value to 1500±50 cP. Then, the conveying pipeline L4 is opened to pump the qualified slurry to the finished slurry tank 3B.
[0065] (2) The substrate is drawn out by the unwinding roller 21 and preheated to the coating temperature of 60°C by the preheating roller 6; the slurry stored in the finished slurry tank 3B is transported to the slot coating die 5 and coated on the surface of the preheated substrate by the slot coating die 5 to form a wet film with a thickness of 150μm. (3) The coated substrate enters the gradient curing chamber and undergoes gradient curing in sequence through the infrared drying zone 7, the UV curing zone 8, and the low-temperature curing zone 9. The infrared drying zone 7 uses a plate-shaped infrared radiator 10 for initial drying; the UV curing zone 8 uses a dual-wavelength LED array 13 for irradiation; and the low-temperature curing zone 9 uses a layered hot air circulation system for curing. The processing parameters for the infrared drying zone 7 are: initial drying at 80.0℃ (±0.3℃) for 1 min; and the processing parameters for the UV curing zone 8 are: under nitrogen protection, with oxygen content controlled at <50ppm, irradiation is performed using a dual-wavelength LED array 13, where the two wavelengths of the dual-wavelength LED array 13 are... 365nm and 395nm; along the direction of travel of the coated substrate, there are high-irradiation sections and low-irradiation sections in sequence; the intensity of the high-irradiation section is 90mW / cm², the intensity of the low-irradiation section is 35mW / cm², and the total irradiation time is 10-30s; the flow rate of the bidirectional tangential air inlet 17 in the Z-type nitrogen flow field system is 10L / min, the airflow velocity of the central top suction exhaust port 16 is 0.8m / s, and the oxygen content is maintained at 42ppm; the processing parameters of the low-temperature curing zone 9 are: a layered hot air circulation system is adopted, the lower hot air spray plate 18 has a wind speed of 15m / s and a wind temperature of 50℃; the upper micro-negative pressure return air channel has a negative pressure of -5 to -20Pa, and curing is carried out at 50℃ for 8min. The method also includes temperature control using temperature zone isolation components: a negative pressure air curtain 12 is installed between the infrared drying zone 7 and the UV curing zone 8, with a pressure difference of -30Pa; a liftable ceramic fiber baffle 14 with a thermal conductivity of 0.04W / m·K is installed between the UV curing zone 8 and the low-temperature curing zone 9; each temperature zone is independently temperature controlled, with a temperature difference ≤±1℃.
[0066] (4) The cured substrate is electrostatically peeled off by an electrostatic adsorption roller 19 with spiral microgrooves on its surface. The peeled film is then wound up by a dual-station winding machine 20 to obtain a composite solid electrolyte membrane. The spiral microgrooves on the surface of the electrostatic adsorption roller 19 have a depth of 100 μm and a spiral angle of 25°. An adjustable voltage of 3 kV is applied to the electrostatic adsorption roller 19. The peeled film is wound up by the dual-station winding machine 20 at a production speed of 8 m / min.
[0067] The production process employs an online quality monitoring module for inspection, including: a thickness laser micrometer 11 located at the outlet of the infrared drying zone 7 for real-time monitoring of film thickness; and an ultraviolet imager 15 located at the outlet of the UV curing zone 8 for detecting curing uniformity. Both the thickness laser micrometer 11 and the ultraviolet imager 15 are connected to the central controller, and the detection data is used to provide real-time feedback for adjusting the gap of the slit coating die 5 and the process conditions of each curing zone.
[0068] Film thickness uniformity: ±1.2 μm (CV value 1.5%); Ionic conductivity (25℃): 1.32 × 10⁻⁶ -4 S / cm; Yield: 98.8%; Dendrite tolerance time: 530h; Tensile strength: 8.3MPa.
[0069] Example 3 The only difference between this embodiment and embodiment 2 is that the production speed in step (4) is increased to 10 m / min.
[0070] Film thickness uniformity: ±1.4 μm (CV value 1.9%); Ionic conductivity (25℃): 1.28 × 10⁻⁶ -4 S / cm; Yield: 98.5%; Dendrite tolerance time: 515 h; Tensile strength: 8.1 MPa.
[0071] Example 4 The only difference between this embodiment and embodiment 2 is that the thickness of the wet film formed in step (2) is 80 μm.
[0072] Film thickness uniformity: ±0.9 μm (CV value 1.1%); Ionic conductivity (25℃): 1.35 × 10⁻⁶ -4 S / cm; Yield: 99.2%; Dendrite tolerance time: 540h; Tensile strength: 8.0 MPa.
[0073] Example 5 The only difference between this embodiment and embodiment 2 is that: (1) Adjustment of slurry formulation: Based on the total mass of slurry as 100%, the solvent acetonitrile accounts for 85%, the total solid components are 15%, and the solid components are LLZO: 50%, PETA: 15%, PEO: 13%, LiTFSI: 18%, borate ester: 2%, initiator: 2%.
[0074] (2) Pretreatment path: Path three (sand milling + ultrasonic series) is adopted to cope with the dispersion difficulty caused by high filler. The treated slurry enters the intermediate buffer tank 3A with an initial viscosity of 2200 cP. The central controller executes the reflux reprocessing mode, opens the first reflux pipeline L5, and pumps part of the slurry back to the sand mill 1 for secondary grinding and dilution. After returning, the viscosity drops to 1950 cP, and is then stabilized to the target value of 1800±50 cP through precise adjustment.
[0075] (3) UV curing parameter adjustment: In order to cope with the influence of high filler on UV transmittance, the intensity of the high irradiation section of the UV curing zone is increased to 100 mW / cm².
[0076] Test results: Film thickness uniformity: ±1.5 μm (CV value 2.0%); Ionic conductivity (25℃): 1.25 × 10⁻⁶ -4 S / cm; Tensile strength: 9.1 MPa; Dendrite tolerance time: 505h; Yield: 98.3%.
[0077] Example 6 The only difference between this embodiment and Embodiment 2 is that the inlet flow rate of the Z-shaped nitrogen flow field is adjusted to 5 L / min. The oxygen content is stabilized at 48 ppm (<50 ppm); the ultraviolet imager (15) shows a curing uniformity of 98.7%. Test results: Film thickness uniformity: ±1.3 μm (CV value 1.7%); Ionic conductivity (25℃): 1.30 × 10⁻⁶ -4 S / cm; roll-to-roll yield: 98.6%; dendrite tolerance time: 510h; tensile strength: 8.2 MPa. Ultraviolet imaging (15) showed a curing uniformity of 98.7%.
[0078] Example 7 The only difference between this embodiment and embodiment 2 is that the groove depth of the electrostatic adsorption roller (19) is 200μm, the helix angle is 30°, and the voltage is 5kV.
[0079] Test results: Film thickness uniformity: ±1.1 μm (CV value 1.4%); Ionic conductivity (25℃): 1.33 × 10⁻⁶ -4 S / cm; roll-to-roll yield: 99.0%; dendrite tolerance time: 525h; tensile strength: 8.5 MPa.
[0080] Example 8 The only difference between this embodiment and embodiment 2 is step (1): Using the second path, the slurry raw material is treated in the ultrasonic dispersion tank 2 and then enters the intermediate buffer tank 3A through the second feed pipeline L2. The initial viscosity of the slurry entering the tank is 2000 cP, which is within the target viscosity range. A trace amount of solvent is added to stabilize the viscosity at 1500±50 cP before pumping it to the finished slurry tank 3B.
[0081] (Subsequent coating, curing, and peeling parameters are the same as in Example 2) Test results: Film thickness uniformity: ±1.3 μm (CV value 1.6%); Ionic conductivity (25℃): 1.29 × 10⁻⁶ -4 S / cm; roll-to-roll yield: 98.6%; dendrite tolerance time: 520h; tensile strength: 8.2 MPa.
[0082] Example 9 The only difference between this embodiment and embodiment 2 is step (1): Using path three, the slurry raw material is processed sequentially through a sand mill 1 and an ultrasonic dispersion tank 2 in series, and then enters the intermediate buffer tank 3A through the second feed pipeline L2. The viscosity of the slurry entering the tank is 1650 cP, which is within the target viscosity range. The central controller executes a precision adjustment mode, adds a small amount of solvent, and fine-tunes the viscosity to 1500±50 cP before pumping it to the finished slurry tank 3B.
[0083] (Subsequent coating, curing, and peeling parameters are the same as in Example 2) Test results: Film thickness uniformity: ±1.0 μm (CV value 1.2%); Ionic conductivity (25℃): 1.34 × 10⁻⁶ -4 S / cm; roll-to-roll yield: 99.1%; dendrite tolerance time: 535h; tensile strength: 8.4 MPa. Serial processing achieves better dispersion uniformity.
[0084] Comparative Example 1 Using the same slurry formulation as in Example 2, production was carried out on conventional thermosetting equipment: after the slurry was applied to the substrate, it was continuously thermo-cured in an oven at 80°C for 12 hours, followed by mechanical peeling and winding.
[0085] Film thickness uniformity: ±5.8 μm (CV value 7.3%); Ionic conductivity (25℃): 0.85 × 10⁻⁶ -4 S / cm; roll-to-roll yield: 86.2%; dendrite tolerance time: 95h; tensile strength: 6.0 MPa.
[0086] Table 1
[0087] Table 1 data fully validates the synergistic effect and industrialization value of this patented innovative design. Under the synergistic effect of the gradient curing chamber (infrared drying-ultra-low oxygen UV curing-layer curing) and the precision temperature zone isolation system (negative pressure air curtain + liftable ceramic fiber baffle), the film thickness CV value of all embodiments is ≤2% (as low as 1.1%), breaking through the accuracy limit of ±5μm of traditional processes. In particular, Embodiment 4 achieves an accuracy of ±0.9μm under the condition of 80μm ultrathin film, directly verifying the closed-loop control advantages of the thickness laser micrometer (±0.5μm) and the online viscosity feedback system set in the intermediate buffer tank 3A.
[0088] More importantly, the Z-shaped nitrogen flow field maintains an oxygen content of 48ppm even under critical conditions (5L / min inlet flow rate in Example 6), ensuring dendrite tolerance time of >500h (540h in Example 4), completely solving the curing defect problem caused by oxygen inhibition; while the spiral microgroove electrostatic adsorption roller design (200μm groove depth + 30° spiral angle in Example 7) increases the yield to 99% and reduces peel tension by 20%, achieving an industry breakthrough of "near-zero damage" under high-speed winding.
[0089] Of particular note is that, under conditions of high solids content and high viscosity (Example 5), the equipment still controlled the film thickness CV value at the 2.0% boundary by dynamically adjusting the UV irradiation intensity (100mW / cm²) and the die gap, and the tensile strength increased to 9.1MPa. This proves that the gradient curing chamber and intelligent viscosity control successfully suppressed the phase separation tendency of the high filler system.
[0090] Compared with the traditional thermosetting process (Comparative Example 1), this equipment improves ionic conductivity by 55% and yield by 12.6%, achieving a "triple leap" in high precision, high performance, and high yield from the root.
[0091] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A high-efficiency continuous production system for composite solid electrolyte membranes, characterized in that, It includes a slurry supply unit, an unwinding unit, a coating unit, a gradient curing unit, and a peel and rewind unit; The slurry supply unit includes a slurry processing device, an intermediate buffer tank (3A), and a finished slurry tank (3B) connected together; the slurry processing device includes a sand mill (1) and an ultrasonic dispersion tank (2), and the sand mill (1) and the ultrasonic dispersion tank (2) can be selectively connected to the intermediate buffer tank (3A) in series or in parallel; the intermediate buffer tank (3A) is equipped with an online viscosity feedback system (4) and an additive feeding port, and the online viscosity feedback system (4) is connected to the central controller signal. The unwinding unit includes an unwinding roller (21) for unwinding the substrate; The coating unit includes a preheating roller (6) and a slot coating die (5) arranged sequentially along the substrate travel direction; the preheating roller (6) is located downstream of the unwinding roller (21) and is used to transport and preheat the substrate; the slot coating die (5) is connected to the outlet of the finished slurry tank (3B) and is located on one side of the preheating roller (6) to coat the finished slurry onto the preheated substrate surface on the preheating roller (6) to form a wet film; The gradient curing unit includes a gradient curing chamber, which is provided with an infrared drying zone (7), a UV curing zone (8) and a low-temperature curing zone (9) in sequence along the direction of travel of the coated substrate, for gradient curing of the coated substrate; The infrared drying zone (7) is equipped with a plate-shaped infrared radiator (10); the UV curing zone (8) is equipped with a dual-wavelength LED array (13); and the low-temperature curing zone (9) is equipped with a layered hot air circulation system. The peeling and winding unit includes an electrostatic adsorption roller (19) with spiral microgrooves on its surface and a dual-station winding machine (20) for electrostatic peeling and winding.
2. The high-efficiency continuous production system for composite solid electrolyte membranes according to claim 1, characterized in that, The outlet of the sand mill (1) is connected to the inlet of the intermediate buffer tank (3A) through the first feed pipe (L1) and to the inlet of the ultrasonic dispersion tank (2) through the first series pipe (L3); the outlet of the ultrasonic dispersion tank (2) is connected to the inlet of the intermediate buffer tank (3A) through the second feed pipe (L2). The outlet of the intermediate buffer tank (3A) is connected to the inlet of the finished slurry tank (3B) via a conveying pipeline (L4); The intermediate buffer tank (3A) is also provided with a first reflux pipeline (L5) and a second reflux pipeline (L6). The first reflux pipeline (L5) is connected to the feed inlet of the sand mill (1), and the second reflux pipeline (L6) is connected to the feed inlet of the ultrasonic dispersion tank (2).
3. The high-efficiency continuous production system for composite solid electrolyte membranes according to claim 2, characterized in that, Controllable valves are provided on the first feeding pipeline (L1), the second feeding pipeline (L2), the first series pipeline (L3), the conveying pipeline (L4), the first return pipeline (L5), and the second return pipeline (L6); The controllable valve is operated by a central controller, and by switching its opening and closing states, three slurry pretreatment process paths can be formed: Path 1: Open the controllable valve on the first feed line (L1), close the controllable valves on the first series line (L3) and the second feed line (L2), and the slurry raw material enters the intermediate buffer tank (3A) directly after being processed by the sand mill (1). Path 2: Open the controllable valve on the second feed line (L2), close the controllable valves on the first feed line (L1) and the first series line (L3), and the slurry raw material enters the intermediate buffer tank (3A) directly after being processed by the ultrasonic dispersion tank (2). Path 3: Open the controllable valves on the first series pipeline (L3) and the second feed pipeline (L2), and close the controllable valve on the first feed pipeline (L1). The slurry raw material is processed in series by the sand mill (1) and the ultrasonic dispersion tank (2) and then enters the intermediate buffer tank (3A).
4. The high-efficiency continuous production system for composite solid electrolyte membranes according to claim 3, characterized in that, The central controller is used to perform graded control on the slurry in the intermediate buffer tank (3A) based on the real-time monitoring data of the online viscosity feedback system (4): If the viscosity of the slurry is within the preset target viscosity range for coating, the additive is added to the intermediate buffer tank (3A) through the additive feeding port for online precision adjustment until the viscosity stabilizes at the target value. Then, the controllable valve on the delivery pipeline (L4) is opened to pump the adjusted slurry to the finished slurry tank (3B). If the viscosity value of the slurry is not within the preset coating target viscosity range, control the opening of the controllable valve on the first return pipeline (L5) or the second return pipeline (L6) to pump the slurry in the intermediate buffer tank (3A) back to the sand mill (1) or the ultrasonic dispersion tank (2) for redispersion treatment.
5. The high-efficiency continuous production system for composite solid electrolyte membranes according to claim 1, characterized in that, The gradient curing chamber is equipped with a temperature zone isolation component: a negative pressure air curtain (12) is provided between the infrared drying zone (7) and the UV curing zone (8), with a pressure difference of -10 to -50 Pa; a liftable ceramic fiber baffle (14) is provided between the UV curing zone (8) and the low temperature curing zone (9), with a thermal conductivity ≤0.05 W / m·K; each temperature zone is independently temperature controlled, with a temperature difference ≤±1℃; The temperature of the plate-shaped infrared radiator (10) in the infrared drying zone (7) is controlled at 79.5-80.5℃; The UV curing area (8) has dual wavelengths of 365nm and 395nm respectively in the dual-wavelength LED array (13); along the direction of travel of the coated substrate, a high-irradiation section and a low-irradiation section are provided in sequence; the high-irradiation section is 80-100mW / cm²; the low-irradiation section is 20-40mW / cm². The UV curing zone is also equipped with a Z-type nitrogen flow field system, including a bidirectional tangential air inlet (17) and a central top-suction exhaust port (16). The flow rate of the bidirectional tangential air inlet (17) is 5-20 L / min, and the airflow velocity of the central top-suction exhaust port (16) is 0.5-2 m / s, maintaining an oxygen content of <50 ppm. The low-temperature curing zone adopts a layered hot air circulation system. The lower part is equipped with a hot air jet plate (18) with a wind speed of 10-20m / s and a wind temperature of 49-51℃. The upper part has a micro-negative pressure return air channel with a negative pressure of -5 to -20Pa.
6. The high-efficiency continuous production system for composite solid electrolyte membranes according to claim 1, characterized in that, The system also includes an online quality monitoring module, comprising: A thickness laser micrometer (11) is installed at the outlet of the infrared drying zone (7) for real-time monitoring of film thickness; An ultraviolet imager (15) is installed at the outlet of the UV curing zone (8) to detect curing uniformity; The thickness laser micrometer (11) and the ultraviolet imager (15) are both connected to the central controller. The detection data is used to provide real-time feedback and adjust the gap of the slit coating die (5) and the process conditions of each curing zone.
7. The high-efficiency continuous production system for composite solid electrolyte membranes according to claim 1, characterized in that, The electrostatic adsorption roller (19) is located downstream of the outlet of the gradient curing chamber, and the dual-station winding machine (20) is located downstream of the electrostatic adsorption roller (19). The depth of the spiral microgrooves on the surface of the electrostatic adsorption roller (19) is 50-200μm, the spiral angle is 15°-30°, and the voltage of the electrostatic adsorption roller (19) is 0.5-5kV.
8. A highly efficient continuous production process for composite solid electrolyte membranes, characterized in that, The high-efficiency continuous production system for composite solid electrolyte membranes as described in any one of claims 1-7 includes the following steps: (1) After the slurry raw material is processed by a sand mill (1) and / or an ultrasonic dispersion tank (2), it is transported to the intermediate buffer tank (3A). After viscosity adjustment by the online viscosity feedback system (4) controlled by the central controller signal and the additive feeding port, it is transported to the finished slurry tank (3B) for use. (2) The substrate is drawn out by the unwinding roller (21) and preheated to the coating temperature by the preheating roller (6); the slurry stored in the finished slurry tank (3B) is conveyed to the slot coating die (5) and coated on the surface of the preheated substrate by the slot coating die (5) to form a wet film. (3) The coated substrate enters the gradient curing chamber and undergoes gradient curing in sequence through the infrared drying zone (7), the UV curing zone (8) and the low temperature curing zone (9); wherein, the infrared drying zone (7) uses a plate-shaped infrared radiator (10) for preliminary drying; the UV curing zone (8) uses a dual-wavelength LED array (13) for irradiation treatment; and the low temperature curing zone (9) uses a layered hot air circulation system for curing treatment. (4) The cured substrate is electrostatically peeled off by an electrostatic adsorption roller (19) with spiral microgrooves on its surface. The peeled film is then wound up by a dual-station winding machine (20) to obtain the composite solid electrolyte membrane.
9. The efficient continuous production process for composite solid electrolyte membranes according to claim 8, characterized in that, Step (3) specifically includes: the coated substrate is placed into a gradient curing chamber and sequentially passes through an infrared drying zone (7), a UV curing zone (8), and a low-temperature curing zone (9); wherein, the processing parameters of the infrared drying zone (7) are: preliminary drying at 79.5-80.5℃ for 1-2 minutes; the processing parameters of the UV curing zone (8) are: under nitrogen protection, the oxygen content is controlled to <50ppm, and irradiation is performed using a dual-wavelength LED array (13), the dual wavelengths of the dual-wavelength LED array (13) are 365nm and 395nm respectively; along the direction of travel of the coated substrate, a high irradiation section and a low irradiation section are sequentially provided; wherein the intensity of the high irradiation section is 80-100mW / cm², the intensity of the low irradiation section is 20-40mW / cm², and the total irradiation time is 10-30s; the processing parameters of the low-temperature curing zone (9) are: using a layered hot air circulation system, curing at 49-51℃ for 5-10 minutes; In step (2), the coating temperature is 55-65℃; the thickness of the wet film is 50-200μm; Step (4) specifically includes: applying an adjustable voltage of 0.5-5kV to the electrostatic adsorption roller (19), and the peeled film is wound up by a dual-station winding machine (20) at a production speed of 5-10m / min; Step (1) specifically includes: the central controller selects and controls the controllable valves on the corresponding pipelines according to the formula characteristics, so that the slurry is processed in one of the following three paths: Path 1: After being processed by the sand mill (1), the slurry enters the intermediate buffer tank (3A) through the first feed pipeline (L1); Path 2: After being processed by the ultrasonic dispersion tank (2), the slurry enters the intermediate buffer tank (3A) through the second feeding pipeline (L2). Path 3: The slurry is processed in series by a sand mill (1) and an ultrasonic dispersion tank (2), and then enters the intermediate buffer tank (3A) through the second feed pipeline (L2). The viscosity of the slurry entering the intermediate buffer tank (3A) is monitored in real time by the online viscosity feedback system (4), and graded control is performed by the central controller: A. If the viscosity is within the preset coating target viscosity range, add the additive into the tank through the additive feeding port until the viscosity stabilizes at the target viscosity value. Then, turn on the delivery pipeline (L4) to pump the qualified slurry to the finished slurry tank (3B). B. If the viscosity is not within the preset target viscosity range for coating, the controllable valve on the first return pipeline (L5) or the second return pipeline (L6) is opened to pump the slurry back to the sand mill (1) or the ultrasonic dispersion tank (2) for redispersion treatment. After treatment, it is returned to the intermediate buffer tank (3A) for viscosity adjustment again. The target viscosity value is 500-2000 cP.
10. The application of a high-efficiency continuous production system for composite solid electrolyte membranes as described in any one of claims 1-7, or the high-efficiency continuous production process for composite solid electrolyte membranes as described in any one of claims 8-9, in the continuous production of composite solid electrolyte membranes for solid-state lithium batteries.
Citation Information
Patent Citations
Solid electrolyte composite membrane as well as preparation method and application thereof
CN115020801A
Solid electrolyte film and its manufacturing method, equipment, electrode membrane assembly, and fuel cell
JP2007042590A